A Galinstan-Filled Capillary Probe for Thermal Conductivity Measurements and its Application to Molten Eutectic KNO3-NaNO3-NO2 (HTS) up to 700 K - Le,Brun N; Markides,CNM (International Journal of Thermophysics, 2015)
The successful measurement of the thermal conductivity of molten salts isa challenging undertaking due to the electrically conducting and possibly alsoaggressive nature of the materials, as well as the elevated temperatures atwhich these data are required. For accurate and reproducible measurementsit is important to develop a suitable experimental apparatus and methodology.In this study we explore a modified version of the transient hot-wiremethod, which employs a molten-metal-filled capillary in order to circumventsome of the issues encountered in previous studies. Specifically, by using anovel flexible U-shaped quartz-capillary, filled with a eutectic mixture of gallium,indium and tin, commercially known as Galinstan, we proceed to measurethe thermal conductivity of molten eutectic KNO3−NaNO3−NaNO2.The new probe is demonstrated as being able to measure the thermal conductivityof this molten salt, which is found to range from 0.48 W/m K at500 K to 0.47 W/m K at close to 700 K, with an overall expanded uncertainty(95% confidence) of 3.1%. The quartz is found to retain its electricallyinsulating properties and no current leakage is detected in the sample overthe investigated temperature range. The thermal conductivity data reportedin the present study are also used to elucidate a partial disagreement foundin the literature for this material.